Indetectabilidade sem intransmissibilidade: fragmentações do conceito entre a clínica e a vivência - Cruz, Jeneson Tavares da (Universidade do Vale do Rio dos Sinos, 2025)
This dissertation is the result of a study on the concept Undetectable = Untransmittable (U=U) in the lives of gay and bisexual men living with HIV (GBMLWH) who have achieved an undetectable viral load, as well as from the perspective of healthcare professionals working in two specialized HIV services located in Porto Alegre, Brazil, and its metropolitan region. The main objective was to investigate the meanings and interpretations attributed to U=U in the lives of GBMLWH, and to understand how this concept has been constructed and communicated within clinical contexts. U=U is a prevention strategy which states that people living with HIV who adhere to antiretroviral therapy (ART) and reach an undetectable viral load do not transmit the virus through sexual contact. Brazil is internationally recognized for offering ART free of charge through its public healthcare system called Sistema Único de Saúde (SUS) since 1996. In 2019, the country issued an informational note reinforcing the importance of recognizing U=U, affirming that such knowledge contributes positively to the interpersonal relationships of people living with HIV, opens new possibilities for life with the virus, and helps to combat stigma. The field research was qualitative in nature and based on the narratives of 18 participants — 11 GBMLWH and 7 healthcare professionals — which led to the development of two scientific articles. The first article, focused on the narratives of GBMLWH, discusses the meanings and interpretations of U=U in the experiences of those with an undetectable viral load. The study reveals that understanding “undetectability” does not always consistently translate into an understanding of “untransmittability.” In order for the transformative potential of the U=U message to be fully realized in combating HIV-related stigma, the article emphasizes the need for improved communication, even suggesting that the message be reframed as “U=0” to better highlight the notion of zero sexual transmission risk. The second article examines, based on the narratives of both GBMLWH and healthcare professionals, how knowledge about U=U is constructed, interpreted, and negotiated between these two groups. The study reveals a fragmented and frequently misaligned understanding of the concept, highlighting the urgent need for clearer communication and for validating the term "untransmittable" as a strategy to empower patients, promote sexual autonomy, and confront stigma. The findings suggest that although U=U is a prevention strategy capable of improving quality of life and well-being for people living with HIV, its effectiveness is limited by stigma and misinformation. Even in settings where the concept should be more solidified — such as among people with an undetectable viral load and in patient-provider relationships within specialized services — distrust and misalignment with scientific knowledge persist. There is a clear consensus regarding the goal of achieving an undetectable viral load through ART, as this preserves the immune system and prevents progression to aids. However, the second part of the equation — the condition of being untransmittable — remains poorly understood, insufficiently internalized, and ineffectively communicated in clinical environments, as if, in the end, the equation were U≠U.
Keywords: HIV; Indetectabilidade; Intransmissibilidade; Undetectability; Non-transferability; ACCNPQ::Ciências da Saúde::Saúde Coletiva